Predicting the accuracy of a diagnosis of Alzheimer's disease with 99mTc HMPAO single photon emission computed tomography. - Dougall, N; Nobili, F; Ebmeier, K (2004)
The current clinical practice of reporting images obtained with single photon emission computed tomography (SPECT) with 99mTc-d,l-hexamethylpropylene amine oxime (99mTc HMPAO) images was examined by having 16 experts evaluate the appearance of SPECT images in patients with probable Alzheimer type dementia (ATD), patients with major depressive episode (DSM-IV), and healthy volunteers. The experts rated diagnostic criteria of scan appearance in respect of importance for their individual diagnostic practice. Experts were nuclear medicine specialists, psychiatrists and physicists taking part in a European multi-centre collaborative project. They examined 158 perfusion scans and then the same perfusion scans together with statistical parametric maps (SPMs). The sensitivity of experts' diagnostic judgments was significantly and negatively correlated with the importance they attributed to reduced regional perfusion in the parietal lobes. A corresponding positive correlation was observed for diagnostic specificity against depressed and healthy volunteers. Similar results were observed with SPMs, where in addition area under the receiver operating characteristic (ROC) curve was significantly reduced with raters' increased diagnostic reliance on frontal lobe perfusion deficits. Sensitivity was greater with SPM for patients younger than 70 years and with dementia severity. The more importance experts placed on parietal (symmetrical) perfusion deficits, the less sensitive and the more specific their diagnostic judgment was. Using multiple raters in large patient samples may provide a way of identifying successful explicit diagnostic strategies for clinical image analysis.